2020
DOI: 10.3917/redp.305.0021
|View full text |Cite
|
Sign up to set email alerts
|

On Some k -scoring Rules for Committee Elections: Agreement and Condorcet Principle

Abstract: Given a collection of individual preferences on a set of candidates and a desired number of winners, a multi-winner voting rule outputs groups of winners, which we call committees. In this paper, we consider five multi-winner voting rules widely studied in the literature of social choice theory: the k-Plurality rule, the k-Borda rule, the k-Negative Plurality rule, the Bloc rule, and the Chamberlin-Courant rule. The objective of this paper is to provide a comparison of these multi-winner voting rules according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As we only deal with large electorates, we follow a procedure that was developed in Cervone et al (2005). This technique which is based on the computation of polytope volumes has recently been used in many research papers; see among others Diss andGehrlein (2015, 2012), Diss et al (2020Diss et al ( , 2018, El Ouafdi et al (2020), Gehrlein et al (2015), Kamwa (2019), Kamwa and Moyouwou (2021), Kamwa and Valognes (2017), Moyouwou and Tchantcho (2015). In the online supplementary material we report Propositions 8 to 10 which give the probability representations that we obtain from this technique.…”
Section: Computation Resultsmentioning
confidence: 99%
“…As we only deal with large electorates, we follow a procedure that was developed in Cervone et al (2005). This technique which is based on the computation of polytope volumes has recently been used in many research papers; see among others Diss andGehrlein (2015, 2012), Diss et al (2020Diss et al ( , 2018, El Ouafdi et al (2020), Gehrlein et al (2015), Kamwa (2019), Kamwa and Moyouwou (2021), Kamwa and Valognes (2017), Moyouwou and Tchantcho (2015). In the online supplementary material we report Propositions 8 to 10 which give the probability representations that we obtain from this technique.…”
Section: Computation Resultsmentioning
confidence: 99%
“…But the volume computation was already substantially improved by the descent algorithm described in 5 . Examples of Normaliz being used for voting theory computations by independent authors can be found in 6 , 7 and 8 . The purpose of this paper is to present precise probability computations in five candidates elections under the assumption of the Impartial Anonymous Culture (IAC).…”
Section: Introductionmentioning
confidence: 99%
“…But the volume computation was already substantially improved by the descent algorithm described in [7]. Examples of Normaliz being used for voting theory computations by independent authors can be found in [3], [4] and [14].…”
Section: Introductionmentioning
confidence: 99%